Determination of epacadostat, a novel IDO1 inhibitor in mouse plasma by LC–MS/MS and its application to a pharmacokinetic study in mice. (11th August 2016) - Dhiman, Vinay; Giri, Kalpesh Kumar; S, Suresh P.; Zainuddin, Mohd; Rajagopal, Sriram; Mullangi, Ramesh
Abstract: A sensitive, specific and rapid LC‐ESI‐MS/MS method has been developed and validated for the quantification of epacadostat in mouse plasma using tolbutamide as an internal standard (IS) as per regulatory guidelines. Sample preparation was accomplished through a protein precipitation. Chromatographic separation was performed on an Atlantis dC18 column using a binary gradient using mobile phase A (acetonitrile) and B (0.2% formic acid in water) at a flow rate of 0.90 mL/min. Elution of epacadostat and IS occurred at 2.41 and 2.51 min, respectively. The total chromatographic run time was 3.2 min. A linear response function was established in the concentration range of 1.07–533 ng/mL. The intra‐ and inter‐day accuracy and precision were in the ranges of 1.81–12.9 and 3.80–11.1%, respectively. This novel method has been applied to a pharmacokinetic study in mice.